Design and Synthesis of a Novel 1,2,4-Oxadiazole Derivative: 3-(3-(5-((4-Phenylpiperazin-1-yl)methyl)-1,2,4-oxadiazol-3-yl) phenoxy)propan-2-olamines - Kumar, Deepak; Shinde, Ganesh; Yadav, Vivek; Dalai, Suryakanta; Jangir, Mukesh (Synthesis, 2025)
The synthesis of novel heterocyclic 3-(3-(5-((4-phenylpiperazin-1-yl)methyl)-1,2,4-oxadiazol-3-yl)phenoxy)propan-2-olamine derivatives, in particular piperazine and piperidine derivatives of 1,2,4-oxadiazole, is reported. These compounds are a distinguished motif for biological studies. An effective piperazine and piperidine derivative methodology on 1,2,4-oxadiazole substrates has been developed. This pathway, along with good yields and clean reactions, has a broad substrate scope and provides new biologically useful moieties that can be further investigated for their applicability.
Keywords: oxadiazoles; alkylation; synthesis; heterocycles; cyclization